Formwork-modern techniques : slip forming - Grover, S.K (Global Institute of Construction, 2013)
Formwork-modern techniques : slip forming / Grover, S.K. -- New Delhi: Global Institute of Construction, 2013 624 G883 No. of Copies : 1